KAJIAN ADOPSI TEKNOLOGI BUDIDAYA LEBAH MADU SISTEM ANGON DAN SUMBANGANNYA TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN GRINSING KABUPATEN BATANG STUDY OF MIGRATORY SYSTEM ADOPTION ON BEEKEEPING TECHNOLOGY AND ITS CONTRIBUTION TO FARMER INCOME AT GRINSING DISTRICT, BATANG REGENCY - Sriningsih, Endang; Widarni, Sri (Pembangunan Pedesaan, 2007)
This research had been conducted at Grinsing District, Batang Regency aimed at finding out the adoption level and the relation between internal and external characteristics of farmers with adoption of migratory system on beekeeping technology. Survey method was used with Cluster Random Sampling. The data was used in ordinal scale transferred to internal scale. Data were analyzed with Summated Ratting and Rank Spearmanâs Correlation. The result showed that adoption level in the farmers was high to the system as 73.3%. The farmersinternal characteristics correlated with their adoption of the system were education degree, family dependent, and their farming income with coefficient correlations of 0.261 with value Zig 0.163, 0.275 with value Zig 0.141, and -0.194 with value Zig 0.305, respectively. The external one was frequency of the communication with coefficient correlations of 0.386 with value Zig 0,035. The factor inhibited the adoption was institutional support and capital for business development. Contribution of the system on their household income in dry and wet season was 85.17 and 54.43%, respectively.